Causal Relationships Between Leukocyte Subsets and Adverse Fetal Outcomes: A Mendelian Randomization Study - Hong Chen; Li-Zhen Shao; Ying-Xiong Wang; Zhi-Jie Han; Yong-Heng Wang; Xia Li; Jing-Yu Chen; Tai-Hang Liu (Mediators of Inflammation)
Conclusions: This study provided profound insights into the intricate regulatory mechanisms of leukocyte subsets in neonatal diseases, paving the way for new avenues in the diagnosis and treatment of associated disorders.